DETERMINANTY I MOŻLIWOŚCI PROMOWANIA REGIONÓW - Florek, Magdalena (Wydział Prawa i Administracji UAM, 2001)
On the territorial level a number of attempts are made at adapting marketing instruments, so far implemented in commercial markets, to the needs of regions. Also on the scientific ground more and more often one raises the issue of the so-called territorial marketing, separated as a result of some new functions and applications of marketing. In practice, the most popularly used marketing instrument in this range is promotion. The article presents some ways of implementing promotion in region development, showing at the same time the accompanying limitations and conditions. The notion of a region was treated very broadly and it refers to administrative, social, economic, and ecological units of various sizes, taken as entities. In the article, three main region promotion determinants are pointed at: the exchanged product, the so-called megaproduct, the image of the given region, and of the regional offer addressee. The analysis of these factors determines further possibilities of selecting some specific promotional instruments. Some of them are connected with general promotion, aimed at all groups of recipients, and meant to shape the desired image of the region. The application of the remaining instruments is determined by various goals for selected groups of regional offer respondents.
WAYS AND DETERMINANTS OF REGION PROMOTION